2019
DOI: 10.1016/j.exphem.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The case for plerixafor to replace filgrastim as the optimal agent to mobilize peripheral blood donors for allogeneic hematopoietic cell transplantation

Abstract: Granulocyte colony-stimulating factor (G-CSF)-stimulated peripheral blood progenitor cells (G-PBs) from either a related or unrelated donor continue to be the preferred donor source for most allogeneic hematopoietic cell transplantation (HCT). Recently, the American Society for Blood and Marrow Transplantation has recommended marrow instead of G-PBs as an unrelated graft source due to its lower rate of chronic graft-versus-host disease (cGVHD). However, the use of marrow is limited by both clinical considerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…CXCR4 is widely expressed in the hematopoietic cell compartment 61 . Hence, application of CXCR4 antagonists does not only lead to a mobilization of hematopoietic stem and progenitor cells but is accompanied by marked leukocytosis that affects all hematopoietic lineages including T reg cells 60 , 62 . Moreover, homing into and retention of both, T reg cells 56 and DCs 63 , in the bone marrow have been proposed to be dependent on CXCR4/SDF1α interaction as well as the constitutive expression of VCAM-1 and endothelial selectins 28 .…”
Section: Introductionmentioning
confidence: 99%
“…CXCR4 is widely expressed in the hematopoietic cell compartment 61 . Hence, application of CXCR4 antagonists does not only lead to a mobilization of hematopoietic stem and progenitor cells but is accompanied by marked leukocytosis that affects all hematopoietic lineages including T reg cells 60 , 62 . Moreover, homing into and retention of both, T reg cells 56 and DCs 63 , in the bone marrow have been proposed to be dependent on CXCR4/SDF1α interaction as well as the constitutive expression of VCAM-1 and endothelial selectins 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Immunologic studies have shown higher CD3+ and CD4+ cell counts in grafts mobilized with plerixafor, however there was no increase in the incidence of graft-versus-host disease. 72 Some studies have shown that in allogeneic SCT engraftment of neutrophils and platelets after stem cell mobilization with plerixafor was faster than that with mobilization failure with G-CSF. 67 , 73 …”
Section: Plerixafor For Allogeneic Sctmentioning
confidence: 99%
“…Plerixafor remains the sole CXCR4 antagonist approved by the Food and Drug Administration for this indication. Recent studies have also provided evidence that plerixafor may be an effective alternative to G-CSF mobilization of PB stem cells for healthy allogeneic donors, associated with rapid engraftment and potentially lower rates of cGVHD [21].…”
Section: Discussionmentioning
confidence: 99%